For the love of cod : a father and son's search for Norwegian happiness - Dregni, Eric, 1968- (University of Minnesota Press, 2021)
"Eric Dregni takes his son on a return trip to Norway--the country where he was born fifteen years earlier--to investigate whether it really is the happiest country on Earth"--